Phenomenon-based Learning in Finnish and Vietnamese Upper Secondary School Curriculum for English as a Foreign Language - Nguyen, Hung Phi (2018)
With the central ideology of incorporating real-life events into school concepts, phenomenon-based learning has received wide media coverage and publicity (Sahlberg, 2015; Symeonidis & Schwarz, 2016). This paper, thus, firstly outlines the main characteristics of phenomenon-based learning and considering affiliated learning theories. Then, the present study aims to compare similarities and differences of Finnish and Vietnamese curricula and analyze them from the perspective of phenomenon-based learning. Three selected curricula from two countries have been examined according to four paired dimensions: viewpoint and mission of education, learning goals and objectives of upper general secondary education, content areas, and instructional techniques. The study conducts a qualitative theory-driven content analysis. The findings identify a variety of similarities and differences between Finnish and Vietnamese curricula in the four paired dimensions. The results provide some implications for educators from the perspective of phenomenon- based learning. The enhancement of students’ critical cognitive and socio- emotional capabilities alongside with academic performances was thoroughly discussed on the basis of the findings. This study also suggests the reconsideration of teachers’ autonomy in creating interesting and meaningful learning environments. The findings can provide teachers with pedagogical benefits and insights for lesson designs and directions towards the lifetime and holistic development of students’ intelligence, competencies, agency and motivations. These findings also give some academic ideas on how diversely phenomenon-based learning can be realized in national core curricula.